PEMBUATAN MESIN PEMOTONG BATU UNTUK INDUSTRI ABSTRACT KECIL ORNAMEN BANGUNAN - Hariyanto, V Lilik (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
The voucher program entitled "Manufacturing Ornamental Stone Cutting Machine for Small Building Ornament Industries" aims to increase productivity of the CV. PURBA KRIASTA especially in cutting ornamental stone being produced" It also wants to know the size and productivity of such ornamental stone machine. The steps of this manufacturing ornamental stone cutting machine are planning, machine manufacturing, and training fbr industry partner workers. The planning step includes : (l) designing machine plan draft, (2) calculating the needed materials, and (3) calculating the implementation cost . The machine-manufacturing step includes : (l) material cutting to fit the work draft, (2) welding, (3) assembling, (4) electric installation. (5) machine performance test, and (6) painting. The training for industry partner workers consists of :(l) theory and speech delivery, (2) demonstration of machine using, and (3) machine using practice by the industry partner workers. The result of the voucher program is realization of an ornamental stone cutting machine and skill achievement by the industry partner workers in the machine operation. The ornamental stone cutting machine was made of right-angled iron frame sizing 80x80x7 mm,50x50x5 mm, and 30x30x3 mm, combined with steel plate of 3 mm thick. The machine size is 120 cm length, 60 crn width, and 190 crn height, moved by a I phase electric motor power SEM of I HP and rotation speed of 2800 RPM. The cooling system uses water moved by an aquarium pump. The machinE performance and productivity especially for cutting straight forms has speed of 8 to l0 times faster compared with manual cutting having been done up till now. Key words : stone cutting machine, and small ornamental stone industry.